Imaging the stomatal physiology of somatic embryo-derived peanut leaves by scanning electrochemical microscopy - Parthasarathy, Meera; Singh, Shweta; Hazra, Sulekha; Pillai, Vijayamohanan K. (Analytical and Bioanalytical Chemistry, 2008)
The stomatal physiology, chlorophyll distribution and photosynthetic activity of somatic embryo (SE)- and seedling-derived peanut plants grown in vitro (test tube-grown) and extra vitrum (soil-grown) are investigated using scanning electrochemical microscopy (SECM). This SECM imaging is performed in two different feedback modes, corresponding to oxygen evolution and chlorophyll distribution. More specifically, the oxygen evolution profiles of the in vitro leaves indicate important differences in leaf anatomy between the SE- and seedling-derived leaves. On the other hand, the chlorophyll distribution images show individual stomata of size ca. 27 +/- 5 mu m. Further studies on senescing (aged) leaves reveal interesting voltammograms that vary widely over the stomatal complexes and the surrounding tissues, probably due to the release of electroactive metabolites during chlorophyll breakdown when the leaves turn yellow. Thus, the present investigation could open up new opportunities for characterizing botanical systems using electroanalytical techniques. In addition, it could provide further insights into various areas of current relevance, including signal transduction, cell fate/differentiation and developmental biology.
Keywords: leaf senescence; oxygen evolution; photosynthesis; SECM; somatic embryogenesis; stomata